Occurrence of multiple bisphenol S analogues in children from Shantou, China. (April 2023) - Pan, Yanan; Zhu, Jingcheng; Zhu, Zhenni; Wei, Xin; Zhou, Xiaoyue; Yin, Renli; Jing Li, Adela; Jiao, Xiaoyang; Qiu, Rongliang
Graphical abstract: Higher exposure risk from emerging BPSs along with BPA and BPAs should be underlined for female, younger and abnormal-weighted children from an e-waste recycling city. Abstract: Emerging bisphenol S analogues (BPSs) have gained their application perspectives to replace bisphenol A (BPA) and BPA analogues (BPAs). However, the extent of human exposure and potential health risk from BPSs is rarely known yet. We hypothesized that children living in Shantou, China, a well-known e-waste recycling city, may expose to emerging BPSs together with BPA and BPAs. In this study, BPA, six commonly used BPAs and 11 emerging BPSs were determined simultaneously in 240 urine samples collected from children residing in Shantou. BPA, BPS, bisphenol F, bisphenol AF and three BPSs of 2, 4′-bis(hydroxyphenyl)sulfone, 4-((4-(allyloxy)phenyl)sulfonyl)phenol and diphenylsulfone (DPS) were the urinary predominant bisphenols with detection frequencies of 67–100% in the children. BPA was found at the highest median concentration (3.36 µg/g creatinine) followed by BPS (0.313) and DPS (0.187). It is interesting to find that the girls and children in the younger group (2 ≤ age < 5) had consistently higher concentrations of the seven dominant bisphenols than the boys and these of the older group (5 ≤ age ≤ 10), respectively. The children with under/overweight suffered higher burdens of bisphenol exposure based on medians of estimated daily intakes. Association analysis results indicated that the Shantou children exposed themselves to multiple BPSs along with BPA and BPAs from assumed consumer products and/or contaminated environments.